عزل وتشخيص بعض انواع المكورات العنقودية المتجة لرائحة الابط - Abeer Mohammed (University of Thi-Qar Journal of Science, 2019)
This study included isolation and identification Staphylococcus spp. that cause armpit odor , 90 samples ( Skinswabs) were collected from students of the Faculty of Science, Department of Environment and Pollution in AlMuthannaUniversity,fortheperiodfrom(November2014untilFebruary2015),andincluded40armpitsamples formales and 50 armpit samples for females . It was alerted donors to stop the use of deodorant and inhibitors sweatingbefore 24 hours of sample collection , then diagnosed samples and laboratory diagnostic results showed that emergence of 74 sample ( 30 males and 44 females ) is positive for the gram dye in the form grape clusters , belonging to the typesof Staphylococcus spp. that cause armpit odor ,and then all isolates were subjected to the biochemical tests , the resultshave been obtained 46(62.2%) Staph. epidermidis , 18(24.3%) Staph. aureus, 7(9.5%) Staph. haemolyticus and 3(4.1%)Staph. saprophyticus